Micropropagation Of Curcuma Xanthorrhiza Roxb. And Zingiber Aromaticum Vahl. With Antimicrobial Activities Via Aerated Culture System - Kusumastuti, Melati Yulia (2012)
The aseptic rhizomatous buds of Curcuma xanthorrhiza and Zingiber aromaticum were established by surface sterilizing with 70% ethanol for 20 minutes followed by 50% (v/v) Clorox® for 20 minutes. This procedure produced 100% and 83.3% aseptic buds explants of C. xamthorrhiza and Z. aromaticum respectively. All the aseptic buds of both species survived when cultured on MS medium supplemented with 0.5 mg/L BA and 0.5 mg/L IBA. The number of shoots formed from each shoot explant for both species using MS medium supplemented with 1.0 mg/L BA (C. xanthorrhiza 3..7 shoots per explant; Z. aromaticum 4.3 shoots per explant) was found to be not significantly different when compared with cultures using MS supplemented 0.5 mg/L BA and 0.5 mg/L IBA (C. xanthorrhiza 3.9 shoots per explant; Z. aromaticum 3.0 shoots per explant).